PENENTUAN YURISDIKSI DALAM PENYELESAIAN SENGKETA PERCERAIAN PADA PERKAWINAN CAMPURAN DI INDONESIA DALAM PERSPEKTIF HUKUM PERDATA INTERNASIONAL - Siregar, Anil Refalzey; Kusuma, Putu Riski Ananda; Dantes, Komang Febrinayanti (Jurnal Ilmu Hukum Sui Generis, 2025)
The issue of mixed marriages has serious problems related to the resolution of divorce disputes. With such diversity, there is a tendency for each country to maintain public policy. Determining the jurisdiction of divorce in mixed marriages is often colored by conflict of laws. This study examines how international civil law views divorce cases in mixed marriages. In addition to clearly presenting the results of the research conducted, this study also provides a normative description and is conducted using research methods to provide clarification regarding the issues studied.